Identification of serological markers for pre- and postoperative fasting periods. (April 2019) - Wuensch, Tilo; Quint, Janina; Mueller, Verena; Mueller, Anne; Wizenty, Jonas; Kaffarnik, Magnus; Kern, Barbara; Stockmann, Martin; Biebl, Matthias; Pratschke, Johann; Aigner, Felix
Summary: Background & aims: Prolonged preoperative fasting periods lead to catabolic states and decelerate recovery after surgery. Valid plasma markers reflecting the patients' metabolic state may improve tailored nutrition support before surgery. Within this study, we sought to advance the knowledge on fasting time-sensitive plasma markers that allow the metabolic characterisation of surgical patients for an optimised preoperative metabolic preparation. Methods: Patients scheduled for elective surgery of the upper (n = 23) or lower (n = 27) gastrointestinal tract participated in a prospective observational study. Patients' charateristics and nutritional status were recorded and blood samples were drawn on the day of admission. Further blood samples were collected before skin incision of the surgical procedure, on postoperative day 3 and on the day of discharge. Values of clinical chemistry, electrolytes, hemograms and plasma amino acids were determined and correlated with fasting times. Results: Preoperative fasting times were positively correlated with plasma levels of valine, leucine, serine, α-amino butyric acid, free fatty acids, 3-hydroxy butyric acid and significantly negative correlated with chloride and glutamic acid. Postoperative fasting times were correlated with erythrocytes, leukocytes and plasma levels of albumin, CRP, HDL, asparagine and 3-methylhistidine. The multivariate regression analysis revealed glutamic acid and valine as significant independent predictors of preoperative fasting periods. The regression model showed best performance (sensitivity of 90.91% and specificity of 92.31%) to detect patients fasted for ≥20 h. Conclusion: Valine and glutamic acid appear as independent metabolic markers for accurate prediction of prolonged fasting periods, independent of the overall nutritional status, age or BMI of patients. Highlights: Perioperative nutrition support and reduced fasting times are vital for optimal postoperative recovery. Glutamic acid and valine are the most reliable markers for preoperative fasting periods. Prolonged postoperative fasting is associated with increased plasma CRP levels. Assessing patients' nutritional and fasting status at the time of admission will allow individualized nutrition support.